\[\boxed{\text{593\ (593).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1){\ (a + b)}^{2} + (a - b)^{2} =\]
\[= 2 \cdot (a^{2} + b^{2})\]
\[Преобразуем\ левую\ часть\ \]
\[равенства:\]
\[a^{2} + 2ab + b^{2} + a^{2} - 2ab + b^{2} =\]
\[= 2a^{2} + 2b^{2} = 2 \cdot \left( a^{2} + b^{2} \right)\]
\[2a^{2} + 2b^{2} = 2 \cdot (a^{2} + b^{2})\]
\[2 \cdot \left( a^{2} + b^{2} \right) = 2 \cdot \left( a^{2} + b^{2} \right).\]
\[Тождество\ доказано.\]
\[2)\ (a + b)^{2} - (a - b)^{2} = 4ab\]
\[Преобразуем\ левую\ часть\ \]
\[равенства:\]
\[a^{2} + 2ab + b^{2} - a^{2} + 2ab - b^{2} =\]
\[= 4ab\]
\[2ab + 2ab = 4ab\]
\[4ab = 4ab.\]
\[Тождество\ доказано.\]
\[3)\ a^{2} + b^{2} = (a + b)^{2} - 2ab\]
\[Преобразуем\ правую\ часть\ \]
\[равенства:\]
\[a^{2} + b^{2} = a^{2} + 2ab + b^{2} - 2ab\]
\[a^{2} + b^{2} = a^{2} + b^{2}.\]
\[Тождество\ доказано.\]
\[4)\ \left( a^{2} + b^{2} \right)\left( c^{2} + d^{2} \right) =\]
\[= (ac + bd)^{2} + (ad - bc)^{2}\]
\[Преобразуем\ обе\ части\ \]
\[равенства:\]
\[a^{2}c^{2} + a^{2}d^{2} + b^{2}c^{2} + b^{2}d^{2} =\]
\[a^{2}c^{2} + a^{2}d^{2} + b^{2}c^{2} + b^{2}d^{2} =\]
\[= a^{2}c^{2} + b^{2}d^{2} + a^{2}d^{2} + b^{2}c^{2}\]
\[a^{2}c^{2} + a^{2}d^{2} + b^{2}c^{2} + b^{2}d^{2} =\]
\[= a^{2}c^{2} + a^{2}d^{2} + b^{2}c^{2} + b^{2}d^{2}.\]
\[Тождество\ доказано.\]
\[\boxed{\text{593.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ 8c^{3} - 2c^{2} + 4c - 1 =\]
\[= \left( 8c^{3} + 4c \right) - \left( 2c^{2} + 1 \right) =\]
\[= 4c \cdot \left( 2c^{2} + 1 \right) - 1 \cdot \left( 2c^{2} + 1 \right) =\]
\[= \left( 2c^{2} + 1 \right) \cdot (4c - 1).\]
\[2)\ x^{2}y + x + xy^{2} + y =\]
\[= (x^{2}y + xy^{2} + (x + y) =\]
\[= xy \cdot (x + y) + 1 \cdot (x + y) =\]
\[= (x + y) \cdot (xy + 1).\]
\[3)\ 9a^{2}b - 3a^{2} + 3b^{2} - b =\]
\[= \left( 9a^{2}b + 3b^{2} \right) - \left( 3a^{2} + b \right) =\]
\[= 3b \cdot \left( 3a^{2} + b \right) - 1 \cdot \left( 3a^{2} + b \right) =\]
\[= \left( 3a^{2} + b \right) \cdot (3b - 1).\]
\[4)\ 8a^{2} - 2ab - 4ac + bc =\]
\[= 2a \cdot (4a - b) - c \cdot (4a - b) =\]
\[= (4a - b) \cdot (2a - c).\]
\[5)\ 2b^{3} - 7b^{2}c - 4b + 14c =\]
\[= \left( 2b^{3} - 4b \right) - \left( 7b^{2}c - 14c \right) =\]
\[= 2b \cdot \left( b^{2} - 2 \right) - 7c \cdot \left( b^{2} - 2 \right) =\]
\[= \left( b^{2} - 2 \right) \cdot (2b - 7c).\]
\[6)\ 6x^{5} + 4x^{2}y^{2} - 9x^{3}y - 6y^{3} =\]
\[= \left( 6x^{5} + 4x^{2}y^{2} \right) - \left( 9x^{3}y + 6y^{3} \right) =\]
\[= \left( 3x^{3} + 2y^{2} \right) \cdot \left( 2x^{2} - 3y \right)\text{.\ }\]